Multiple-factor of metabolic disturbances at women of genesial age in a postovariectomy state - L. V. Pokul; I. D. Yevtushenko; Ye. S. Zhabina (Бюллетень сибирской медицины, 2009)
In this article the postovariectomic syndrome is regarded as prediction of metabolic syndrome in women of different age groups. With various clinicodiagnostic analyses it has been estimated that in women with postovariectomic syndrome over 40 metabolic disturbances are observed more frequently.